CURRENT LEARNING CONDITIONS TO SUPPORT THE NEED ANALYSIS OF ENGLISH MATERIALS AT VOCATIONAL SCHOOL - Rismasari Rismasari; Syafryadin Syafryadin; Syahrial Syahrial (Balai Diklat Keagamaan Bandung, 2022)
This research investigated the current learning condition to support the need analysis of English materials for Islamic banking majors at vocational schools. Fifty students of Islamic banking majors and one English teacher were the participants in this study. This study used a mixed-method research design. Researchers collected data from interviews and questionnaires. The researcher created a questionnaire based on the strengths and weaknesses of current situations reviewed from the English materials learning at Islamic banking major. This study found that the current learning condition in learning English at Islamic banking majors at SMKN 4 Lubuklinggau already used English textbooks following the 2013 curriculum, and more than half of the students are also enthusiastic about participating in English learning process. However, it does not meet the students’ and teachers’ needs in the area of learning materials. The English textbooks or materials used are not appropriate for the Islamic banking major. Keywords: Need Analysis; English Materials; Vocational School